2017
DOI: 10.1037/lat0000069
|View full text |Cite
|
Sign up to set email alerts
|

Cultural profiles among Mexican-origin girls: Associations with psychosocial adjustment.

Abstract: Much of the cultural processes research has used single-domain measures of and approaches to cultural orientation, acculturation, and ethnic identity. The current study examined the latent cultural profiles that emerged from the intrapersonal (i.e., ethnic identity and generational status), interpersonal (i.e., language use), and familial (i.e., familial ethnic socialization) domains among 338 Mexican-origin girls in 7th (n ϭ 170; M age ϭ 12.27, SD ϭ .28; 63.6% U.S.-born) and 10th grades (n ϭ 168; M age ϭ 15.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
(63 reference statements)
3
32
0
Order By: Relevance
“…Latinx immigrant parents in the sample used all six ERS strategies. These results illustrate the utility of using measures that capture multiple ERS strategies, including immigration‐related strategies, rather than, as in previous studies (e.g., Gonzales‐Backen et al, ; McGill et al, ), focusing on only one or two. That said, although the parents in the sample used all the strategies, they did so to varying degrees, both among themselves and across strategies.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Latinx immigrant parents in the sample used all six ERS strategies. These results illustrate the utility of using measures that capture multiple ERS strategies, including immigration‐related strategies, rather than, as in previous studies (e.g., Gonzales‐Backen et al, ; McGill et al, ), focusing on only one or two. That said, although the parents in the sample used all the strategies, they did so to varying degrees, both among themselves and across strategies.…”
Section: Discussionsupporting
confidence: 75%
“…Prior work with African American parents has identified the existence of a profile that is characterized exclusively by negative socialization messages, such a promotion of mistrust (Neblett et al, ). Although one of the two prior studies on parents' profiles among Latinx samples did identify a low use of ERS in the profiles (Gonzales‐Backen et al, ), ERS were only examined in terms of cultural socialization; ERS that promote limiting social interactions or not trusting others were not examined. In the present sample of Latinx immigrant parents, this type of profile was not present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the state of the literature in 2006 as outlined by D. Hughes et al (), a review of the literature in the 2010 decade revealed a significant empirical base from which to conclude that a robust and positive association exists between cultural socialization and multiple indicators of positive youth development (see Table ). Findings for this dimension of ethnic–racial socialization overwhelmingly supported cultural socialization as a promotive factor via its positive associations with many indicators of youths' adjustment such as ethnic–racial identity (e.g., Brittian, Umaña‐Taylor, & Derlan, ; Hernández, Conger, Robins, Bacher, & Widaman, ), self‐esteem (e.g., Gonzales‐Backen, Bámaca‐Colbert, Noah, & Rivera, ), academic adjustment (e.g., Banerjee, Harrell, & Johnson, ; Bravo, Umaña‐Taylor, Guimond, Updegraff, & Jahromi, ; Rivas‐Drake & Marchand, ), adaptive coping (e.g., Blackmon, Coyle, Davenport, Owens, & Sparrow, ; McDermott, Umaña‐Taylor, & Martinez‐Fuentes, ), and psychological well‐being (e.g., Nguyen, Wong, Juang, & Park, ). Furthermore, only two of the 236 articles found negative associations and five reported mixed findings, supporting the observations made by D. Hughes et al () that this domain of ethnic–racial socialization was consistently associated with positive outcomes.…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 93%